Impact of Topically Administered Steroids, Antibiotics, and Sodium Hyaluronate on Bleb-Related Infection Onset: The Japan Glaucoma Society Survey of Bleb-Related Infection Report 4 - Hideto Sagara; Tetsuya Yamamoto; Kimihiro Imaizumi; Tetsuju Sekiryu (Journal of Ophthalmology)
Purpose. To investigate the impact of topically administered ophthalmic medications on the onset and severity of bleb-related infections. Methods. Data obtained from 104 eyes of 104 patients with bleb-related infections were analyzed. We assigned an infection stage to each eye (stage 1–4) and analyzed the onset severity. Results. Steroids and antibiotics were routinely administered to 13 (12.5%) and 42 (40.4%) eyes, respectively. The median stage of steroid-administered eyes was 3 versus 1 for eyes without steroid administration (P=0.012). The median duration from surgery to infection for the steroid-administered eyes was 2.0 years versus 5.8 years for eyes without steroid administration (P=0.030). The median duration from surgery to infection for the antibiotic-administered eyes was 6.4 years versus 3.9 years for eyes without antibiotic administration (P=0.025). Multiple logistic regression analysis revealed that infections were severe in the steroid-administered eyes (odds ratio: 4.57). No infections developed within 16 weeks postoperatively. No relationship was detected between sodium hyaluronate and the analyzed factors. Conclusions. Topical steroid administration beyond the immediate postoperative period may affect severe and earlier onset bleb-related infections. Conversely, topical antibiotic administration may be effective in suppressing earlier onset bleb-related infections.